Location-Based Health Service Information System Design (Case Study of Sidoarjo District Health Services) - Wiwit Ardiansyah; Irwan Alnarus Kautsar; Cindy Taurusta (Universitas Muhammadiyah Sidoarjo, 2022)
In this day and age, humans need more efficient technology to facilitate activities in various aspects of life. Health is one of the important aspects of life to ensure human survival. To ensure the quality of public health, it is necessary to have a health service center. Sidoarjo City is one of the areas that has a lot of health services both from the government and from the private sector. Sidoarjo is one of the cities in East Java which is located south of the city of Surabaya. As an effort to promote better health services, a media is needed to make it easier for the public to get information on the location of health services in the Sidoarjo City area. With the current covid-19 pandemic, the author has developed a Web service for a location-based health service information system, where the Web will be designed using the Python programming language and using the Flask framework with output displaying data and the location of hospitals and polyclinics in Sidoarjo City. This system is designed to make it easier for the public to find the nearest service location in Sidoarjo City.